Pojok Baca: Upaya Dalam Menumbuhkan Literasi Membaca Siswa Sekolah Dasar - Suci Zakiyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2023)
The purpose of this study was to determine the role of reading media in an effort to foster students' reading literacy in elementary schools. This type of research uses a qualitative approach. The informants of this study were the principal, homeroom teacher and students of SDN 2 Cintamanik. The data collection instruments used observation sheets, interviews and documentation. The results of this study are that the reading corner has a very important role in efforts to foster students' reading literacy in elementary schools, this is evident from approximately 85% of students who like to visit the reading corner, this shows that there is a media role in the reading corner which can foster reading literacy. elementary school students. The role of the reading corner in cultivating student reading literacy is as a facilitator for reading, as the nearest reading material, a comfortable place to read and a place to read that attracts attention, so that from several of these roles it helps foster students' reading literacy in elementary schools